2011
DOI: 10.1093/czoolo/57.6.781
|View full text |Cite
|
Sign up to set email alerts
|

Age and body size of Rana amurensis from northeastern China

Abstract: Age and body size are two important demographic traits that determine the life history strategies of populations and species. We measured these two parameters of Rana amurensis, at a 900 m and a 500 m altitude site in northeastern China. At the two sites, age at first reproduction was 2 years for males and 3 years for females. The maximum age of males and females at the high-altitude site was 6 and 7 years, and 5 and 7 years at the low-altitude population, respectively. Females were significantly larger than m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Previous studies on amphibian distribution around the world have shown that more precipitation and lower temperatures lead to species richness and increased abundance of amphibians According to our results, were larger (54.64 ± 0.53 mm) and older (7.68 ± 0.24 years) than males (48.13 ± 0.39 mm; 5.89 ± 0.39 years) in both eastern and western clades. The China Wood Frog (Rana chensinensis) the maximum observed longevity was 5 years in males and 4 years in females, respectively (Chen et al 2011). Age at sexual maturity in both sexes was 1 years (Chen et al 2011).…”
Section: The Effects Of Climatic Factors On the Hyrcanian Frogmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on amphibian distribution around the world have shown that more precipitation and lower temperatures lead to species richness and increased abundance of amphibians According to our results, were larger (54.64 ± 0.53 mm) and older (7.68 ± 0.24 years) than males (48.13 ± 0.39 mm; 5.89 ± 0.39 years) in both eastern and western clades. The China Wood Frog (Rana chensinensis) the maximum observed longevity was 5 years in males and 4 years in females, respectively (Chen et al 2011). Age at sexual maturity in both sexes was 1 years (Chen et al 2011).…”
Section: The Effects Of Climatic Factors On the Hyrcanian Frogmentioning
confidence: 99%
“…The China Wood Frog (Rana chensinensis) the maximum observed longevity was 5 years in males and 4 years in females, respectively (Chen et al 2011). Age at sexual maturity in both sexes was 1 years (Chen et al 2011). In the frog endemic to the Middle Taurus Mountain Range, R. holtzi, Ages ranged from 4 to 6 years for males, and from 4 to 7 for females (Guarino et al 2008).…”
Section: The Effects Of Climatic Factors On the Hyrcanian Frogmentioning
confidence: 99%
“…Rana amurensis and Rana dybowskii inhabit similar habitats ( Tong et al, 2019 ). In summer, R. amurensis and R. dybowskii are spread across different areas to procure greater food resources ( Che et al, 2007 ; Chen and Lu, 2011 ). However, these two Rana species are related in terms of their trophic locations, and their primary food source is insects ( Xu et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%